2004
DOI: 10.1016/j.chemphyslip.2004.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of native and oxidized human low-density lipoproteins by the Z-scan technique

Abstract: The nonlinear optical response of human normal and oxidized by Cu2+ low-density lipoproteins particles (LDL), were investigated by the Z-scan technique as a function of temperature and concentration of LDL particles. The Z-scan signals increase linearly with concentration of normal LDL particles, following the usual Beer-Lambert law in a broad range of concentrations. The oxidized LDL particles do not show nonlinear optical response. On the other hand, normal LDL increases its nonlinear optical response as a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 46 publications
0
20
0
4
Order By: Relevance
“…1. As reported in a previous study, 20 the peak-to-valley amplitude, represented by the amplitude of the parameter θ, evaluates the degree of modification of the LDL particles in the sample: the higher the value of θ, the less modified the LDL particle is. The inset in Fig.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…1. As reported in a previous study, 20 the peak-to-valley amplitude, represented by the amplitude of the parameter θ, evaluates the degree of modification of the LDL particles in the sample: the higher the value of θ, the less modified the LDL particle is. The inset in Fig.…”
Section: Resultsmentioning
confidence: 94%
“…The Z-scan apparatus used here is the usual one described elsewhere. 20 Our setup uses a cw laser (Verdi V10, Coherent) of wavelength λ ¼ 532 nm. A mechanical chopper modulates the laser beam incident on the sample, providing nearly square pulses of ∼30 ms (i.e., 30 ms in the "on" state, with the laser lighting the sample, and 30 ms in the "off" state).…”
Section: Z-scan (Zs) In the Milliseconds Time-scale Regimementioning
confidence: 99%
See 2 more Smart Citations
“…al., 17 showed that the linear absorbance coefficient of LDL solutions decreases (in the range between 250 and 550 nm) with the increasing of sample's oxidation degree. This decrease could be associated to the consumption of carotenoids during the oxidation process.…”
Section: Introductionmentioning
confidence: 99%